Personality and intelligence at work : exploring and explaining individual differences at work - Furnham, Adrian (New York Routledge, 2008)
"Personality and Intelligence at Work examines the increasingly controversial role of individual differences in predicting and determining behaviour at work. It combines approaches from organisational psychology and personality theory to critically examine the physical, psychological and psycho-analytic aspects of individual differences, and how they impact on the world of work." "Topics covered include the role of IQ at work as the best predictor of success, but also the importance of increasingly recognised social intelligences such as emotional intelligence (EQ). The significance of personality traits and the impact of temperaments on work performance are also examined, and the methods used to assess work behaviour and potential are reviewed. Psychological tests, which measure personality traits, are questioned as accurate predictors of behaviour at work, alongside other factors such as job satisfaction, productivity, absenteeism and turnover." "This new, thoroughly revised and updated edition of Personality at Work provides a comprehensive review of the relevant literature from psychology, sociology and management science. It will be of interest to students of organisational psychology and business and management studies, as well as HR professionals."--Jacket.
Keywords: Personality and occupation; Prediction of occupational success; Employees -- Psychological testing; Work -- Psychological aspects; Personality and intelligence; Individual differences